2017
DOI: 10.1590/0037-8682-0076-2017
|View full text |Cite
|
Sign up to set email alerts
|

Migration pattern of Toxocara canis larvae in experimentally infected male and female Rattus norvegicus

Abstract: Introduction: Migration of Toxocara canis larvae was investigated in male and female Rattus norvegicus. Methods: Eighteen male and 18 female R. norvegicus were infected with 300 T. canis eggs. Three male and three female rats were euthanized at 3, 7, 10, 15, 30, and 60 days post-infection, and T. canis larvae were recovered by means of organ and tissue digestion. Results: Female rats showed a greater number of larvae in the liver than males. Conclusions: Paratenic host sex influences the migration pattern of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…In addition, the total number of larvae recovered in these organs was higher in females than in males, demonstrating that females are more susceptible than males to T. canis infection. [43]. These results are similar to those reported by our research group, where we observed that the number of larvae in the liver and lung has a dimorphic distribution, as females have a higher number of larvae in the liver than males; although these differences in the parasitic loads at the pulmonary level shows statistically significant differences, where males have a greater number of larvae than females.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the total number of larvae recovered in these organs was higher in females than in males, demonstrating that females are more susceptible than males to T. canis infection. [43]. These results are similar to those reported by our research group, where we observed that the number of larvae in the liver and lung has a dimorphic distribution, as females have a higher number of larvae in the liver than males; although these differences in the parasitic loads at the pulmonary level shows statistically significant differences, where males have a greater number of larvae than females.…”
Section: Discussionsupporting
confidence: 92%
“…Female rats showed a greater number of larvae in the liver than males. 117 Resende et al 82 studied the immunopathology of T. canis infections in mice and found similar larval migration patterns, with innate induction of TH17/TH2 responses during early infection. The migration patterns of T. canis larvae in the gerbil Meriones unguiculatus were similar to the patterns already observed in mice and rats; however, in reinfected animals, more larvae were apparently retained within hepatic granulomas, without evident signs of destruction.…”
Section: Experimental Studies In Nonhuman Paratenic Hostsmentioning
confidence: 93%
“…The beaker was placed in an incubator at 28°C and manually agitated twice daily to ensure the oxygenation of eggs to promote larvae development up to the third stage. After 20 days (the length of time required for thirdstage larval formation), the embryonated eggs were washed three times in saline solution to remove the formalin solution and prepared for infection in the rats (Santos, et al, 2017). Infective P. equorum eggs were collected and kept at 4°C until use.…”
Section: Collection Of Wormsmentioning
confidence: 99%
“…The second division (P. equorum infection division, 18 rats) was allocated into three groups. Group 1: Vehicle, 6 rats received a single oral dose of 1000 P. equorum eggs (Santos, et al, 2017) then received distilled water for 10 days. Group 2: ZnO NPs (30mg/kg), 6 rats received a single oral dose of 1000 P. equorum eggs and were then administered orally 1/ 20 LD 50 of ZnO NPs for 10 consecutive days.…”
Section: Experimental Designmentioning
confidence: 99%